Assessing the compliance of the content of the book of Islamic culture written by Qom province with the religious needs of literate students - Mohsen Dibaei Saber (Universitas Majalengka, 2023)
The aim of this study was to investigate the degree of compliance of the content of the book Islamic Culture written by Qo The descriptive research method included: documentary analysis as well as content analysis and its applied approach. The research community is in the documentary analysis section of all texts related to the religious needs of literate students and in the content analysis section of the book Islamic Culture written by Qom province; Due to the nature of the subject, sampling was omitted and the whole population was examined. The tools for measuring filing forms and content analysis lists have been developed by the researcher Documentary data were analyzed qualitatively and content analysis data were used using descriptive indicators in the Shannon entropy analysis process. The research results showed: 1. The conceptual framework of religious students' religious needs can be classified into three components: cognitive, emotional and functional. Each of these components is also divided into several subcomponents’2. There is no correspondence between the content of the book of Islamic culture of Qom province and the dimensions of religious needs accredited from the perspective of experts. 3.The level of attention to the religious needs of students in the book of Islamic culture written by Qom province is different, so that the most emphasis is on the cognitive component and the least emphasis is on the functional component. province with the religious needs of literate students.